Advances in ecotechnological methods for diffuse nutrient pollution control: wicked issues in agricultural and urban watersheds - Nsenga Kumwimba, Mathieu; Zhu, Bo; Stefanakis, Alexandros I.; Ajibade, Fidelis O.; Dzakpasu, Mawuli; Soana, Elisa; Wang, Tao; Arif, Muhammad; Kavidia Muyembe, Diana; Agboola, Temitope Deborah (Frontiers in Environmental Science, 2023)
Considerable time and funding have been committed to tackling nonpoint source (NPS) pollution in agricultural and urban watersheds (AUWs). Notwithstanding all these efforts, the water quality in many AUWs has not significantly improved. Diffuse nutrient pollution involves the movement of these pollutants between soil and water. Excessive diffuse pollution has been accepted as one of the main causes of failure to attain favorable environmental conditions in freshwater systems. Recently, several technologies and practices have been implemented to manage diffuse pollution, namely: (a) source reduction, (b) pollutant retention over the movement process; (c) nutrient recycling, and (d) purification and restoration of the eutrophic water bodies. This paper synthesized the existing knowledge of key methods to tackle diffuse pollution from AUWs. Furthermore, the predominant purification mechanisms and impacting factors are explored, allowing a comprehensive and critical understanding of different control strategies to improve the management of diffuse pollution.Therefore, potential approaches for strengthening the performance of control technologies for diffuse pollution treatment and remediation are discussed. Although adopting source reduction strategies (e.g., the "4R" approach: right rate, right time, right source, and right placement of nutrients) could efficiently decrease surface runoff and pollutant levels, they may not stop runoff from entering nearby streams. Consequently, comprehensive treatment of agricultural runoff still requires extra process retention strategies. Overall, the findings of this paper showed that treatment system design and operational and environmental factors played crucial but variable roles in diffuse pollution treatment. Moreover, the results showed that combining or integrating constructed wetlands with other control technologies could enhance the comprehensive purification of diffuse pollution compared to using a single method. This review proposes a systematic approach for diffuse pollution control based on three components (water, soil and microbiota) and maximizing the regulating services of agroecosystems via land use/cover types. The current review contributes to the documentation of existing research trends. It sheds light on diffuse pollution control approaches in AUWs, and further encourages the development of this vital field.